The Role of the Trapezius in Stabilization of the Acromioclavicular Joint: A Biomechanical Evaluation. Issue 9 (26th September 2022) - Trudeau, Maxwell T.; Peters, Jonathan J.; Hawthorne, Benjamin C.; Wellington, Ian J.; LeVasseur, Matthew R.; Mancini, Michael R.; Obopilwe, Elifho; Giacomo, Giovanni Di; Cerciello, Simone; Mazzocca, Augustus D.
Background: Acromioclavicular joint (ACJ) injuries are common, and many are adequately treated nonoperatively. Biomechanical studies have mainly focused on static ligamentous stabilizers. Few studies have quantified ACJ stabilization provided by the trapezius. Purpose/Hypothesis: To elucidate the stabilization provided by the trapezius to the ACJ during scapular internal and external rotation (protraction and retraction). It was hypothesized that sequential trapezial resection would result in increasing ACJ instability. Study Design: Controlled laboratory study. Methods: A biomechanical approach was pursued, with 10 cadaveric shoulders with the trapezius anatomically force loaded to normal. The trapezius was then serially transected over 8 trials, which alternated between clavicular defects (CD) and scapular defects (SD); each sequential defect consisted of 25% of the clavicular or scapular trapezial attachment. After each defect, specimens were tested with angle-controlled scapular internal and external rotation (12°) with rotary torque measurements to evaluate ACJ stability. Results: The mean resistance in rotary torque for 12° of scapular internal rotation (protraction) with native specimens was 7.0 ± 2.0 N·m. Overall, internal rotation demonstrated a significant decrease in ACJ stability with trapezial injury ( P < .001). Eight sequential defects resulted in the following significant percentage decreases in rotary torque from native internal rotation: 1.5% (25% CD; 0% SD), 5.6% (25% CD; 25% SD), 5.1% (50% CD; 25% SD), 6.5% (50% CD; 50% SD), 3.8% (75% CD; 50% SD), 7.1% (75% CD; 75% SD), 6.7% (100% CD; 75% SD), and 12.3% (100% CD 100% SD) ( P < .001). The mean resistance in rotary torque for 12° of scapular external rotation (retraction) with native specimens was 7.1 ± 1.7 N·m. External rotation did not demonstrate a significant decrease in ACJ stability with trapezial injury ( P = .596). The 8 sequential defects resulted in decreases in rotary torque from native external rotation of 0%, 3.8%, 4.0%, 3.2%, 3.5%, 3.4%, 4.2%, and 0.7%. Conclusion: Trapezial injury resulted in increased instability in the setting of scapular internal rotation (protraction) of the ACJ. Clinical Relevance: These findings validate the inclusion of deltotrapezial fascial injury consideration in the modified Rockwood classification system. Repair of the trapezial insertion on the ACJ may provide improved outcomes in the setting of ACJ reconstruction.